Die opskrifte van die profeteboeke II - Oberholzer, J. P. (Hervormde teologiese studies, 1985)
This is a continuation of a survey of the headings of the prophetic books. In this article special attention is given to the headings in Jeremiah, the possible motives for their formation and the consequences to be inferred in view of the evaluation of the prophet's words during and after his lifetime.